Tiger Airways’s strategies and competitive advantage / Lailatul Fahmi Abu Bakar - Abu Bakar, Lailatul Fahmi (Faculty of Business and Management, 2013)
Firstly, the purpose of this research is to identify strategies used by Tiger Airways in highly competitive airlines market. In addition, this research also to determine the competitive advantage gained by Tiger Airways in the airline industry. This research focused on the low cost airlines industry and narrow to the airlines company based in Singapore. This research used Porters’ 5 Forces as a determination of strategy in order to identify the internal capabilities of Tiger Airways in airlines industry. Furthermore, to construct the competitive advantage of Tiger Airways, this research use value chain analysis and critical success factor analysis. By using this analysis, the core competencies of Tiger Airways can be defined. In the other hand, the method that being used for this study is by using secondary data and all the data collected is gathered through reading. The data being analyzed by gap analysis and comparison between general practice in airlines industry and Tiger Airways itself. This analysis will be explained and presented in findings of this report.